Antimony recovery from recycled terminals of lead-acid batteries with Na2CO3 and SiC after firstly SsB2O3 formation - Jiménez-Lugos J.C.; Sánchez-Alvarado R.G.; Cruz-Ramírez A.; Romero-Serrano J.A.; Hernández-Ramírez A.; Rivera-Salinas J.E. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Terminals obtained from spent lead-acid batteries in Mexico contain around 2 wt% Sb. The terminals were melted in an electric furnace and then oxygen was injected at 750 °C with a gas flow rate of 2 L/min to produce high purity Sb2O3. The antimony trioxide obtained was treated with a mixture of Na2CO3-SiC at 1000 °C to obtain metallic antimony. The antimony trioxide was reduced by C present in reagents while silicon and sodium formed a slag phase. The amounts of Sb2O3 and SiC were held constant while the Na2CO3 was evaluated in the range from 30 to 42 wt%. The produced antimony and slag were characterized by the X-ray diffraction and SEM-EDS techniques. The addition of 34 wt% Na2CO3 led to the recovery of antimony up to 90.16 wt% (99.57 wt% purity) and the lowest antimony losses in the slag (2 wt%). In addition, the compounds Na2SiO3 and Na2Si2O5 formed in the slag indicated a more stable slag. Na2CO3 contents higher than 38 wt% decreased the antimony recovery since Na2Sb4O7 compound was promoted in the slag. The oxidation and reduction process was modeled in FactSage 7.3 software for a better understanding of the Na2CO3 and SiC additions on the antimony recovery rates and compounds formed in the slag.